Empowering Nueva Ecija’s Farmers through Microfinancing: A Blueprint for Enhancing Financial Literacy and Agricultural Resilience - Fronda, Jennifer G. (International Journal of Economics and Financial Issues, 2024)
This study examines the impact of microfinancing on the livelihoods of farmers in Nueva Ecija, Philippines, with the ultimate goal of formulating a comprehensive financial literacy plan. By analyzing the profile, status, and future prospects of these farmers, the research highlights how microfinance is utilized as a critical tool for economic stability and growth within the agricultural sector. The study identifies significant barriers to accessing microfinancing, including stringent loan conditions and the seasonal uncertainties of farming, which often hinder timely loan repayments and financial planning. Findings suggest that while microfinance has the potential to substantially improve farmers' economic conditions, its effectiveness is currently limited by a lack of financial literacy, inadequate loan flexibility, and insufficient alignment with the specific needs of farmers. As a result, many farmers experience challenges in securing and managing microfinance, thereby affecting their productivity and economic resilience. In response, targeted interventions are proposed to enhance the financial literacy of farmers, coupled with recommendations for microfinance institutions to adapt their products and services to better meet the needs of the agricultural sector. These initiatives aim to empower farmers with the necessary skills and resources to optimize their financial decisions and improve their livelihoods sustainably. The study underscores the need for a collaborative approach involving government bodies, educational institutions, and financial organizations to foster a supportive ecosystem that enhances the viability and sustainability of farming communities in Nueva Ecija.